Alginate-Chitosan Microgel Particles, Water–Oil Interfacial Layers, and Emulsion Stabilization - Aggelos Charisis; Eleni P. Kalogianni (Colloids and Interfaces, 2023)
In this work, alginate-chitosan microgel particles were formed at different pH levels with the aim of using them as viscoelastic interfacial layers, which confer emulsion stability to food systems. The particles’ size and structural characteristics were determined using laser diffraction, confocal laser microscopy (CLSM), and time-domain nuclear magnetic resonance (TD-NMR). The pH affected the microgel characteristics, with larger particles formed at lower pH levels. T2 relaxation measurements with TD-NMR did not reveal differences in the mobility within the particles for the different pH levels, which could have been related to the more or less swollen structure. The rate of adsorption of the particles at the sunflower oil–water interface differed between particles formed at different pH levels, but the equilibrium interfacial tension of all systems was similar. Higher interfacial dilatational viscoelasticity was obtained for the systems at lower pH (3, 4, 5), with G’ reaching 13.6 mN/m (0.1 Hz) at pH 3. The interfacial rheological regime transitioned from a linear elastic regime at lower pH to a linear but more viscoelastic one at higher pH. The thicker, highly elastic interfacial layer at low pH, in combination with the higher charges expected at lower pH, was related to its performance during emulsification and the performance of the emulsion during storage. As revealed by laser diffraction and CLSM, the droplet sizes of emulsions formed at pH 6 and 7 were significantly larger and increased in size during 1 week of storage. CLSM examination of the emulsions revealed bridging flocculation with the higher pH. Nevertheless, all emulsions formed with microgel systems presented macroscopic volumetric stability for periods exceeding 1 week at 25 °C. A potential application of the present systems could be in the formation of stable, low-fat dressings without the addition of any emulsifier, allowing, at the same time, the release of the bioactive compounds for which such particles are known.